PROPOSED MARKETING PLAN FOR SMALL-SIZED ARCHITECTURE FIRM IN BANDUNG - Permatadewi, Carissa
In this era, creative industries have become a major impact on the development of the world economy. In Indonesia, architecture is one part of the creative industry by becoming one of the biggest contributors to total GDP. In the city of Bandung, the architectural business is rapidly expanding to offset the rapid growth of the city due to the development of business opportunities in the city. CP Design Studio as an architecture firm sees Bandung as a city that has great opportunities by seeing the phenomena. To start a business in Bandung, CP Design Studio needs a strategy, moreover because CP Design Studio does not have a connection in Bandung. This study aims to develop the right marketing plan for CP Design Studio in the city of Bandung. To obtain primary data in this research, the author uses observations and in-depth interviews with business competitors in Bandung. The collected data is then used as external data together with PESTEL analysis and Porter’s Five Forces. Internal analysis is used to analyze the company's current internal conditions. Internal analysis uses analysis of marketing mix and STP analysis. After conducting external and external analysis, the author uses SWOT to evaluate the company's internal weaknesses and strengths as well as opportunities and threats in the external environment. The SWOT analysis was then applied to the TOWS matrix to find suitable and relevant alternative marketing strategies. Based on TOWS matrix, the suitable marketing strategies for CP Design Studio are; improving product quality by using technology, make explanations and legal agreements in dividing payment steps to the client, make Online Platforms (website; social media), joining architecture community and events, hire people and do collaboration with other parties, do the competitor analysis regularly, improve the regular business process, and optimize customer feedbacks as a physical evidence. All of these strategies are applied in the new marketing mix elements of CP Design Studio As a conclusion and implementation plan, the marketing strategies are arranged in to a six-month timeline and budgeting plan for CP Design Studio. The timeline contains marketing plans and the budget that should be paid for all the plans.